The Effect of Corporate Social Responsibility Disclosure on Financial Performance with Financial Distress As A Moderating Variable - Adhy Putra, Karya; Puspita, Ayu Fury (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
CSR programs, over time, play a highly important role for companies; as such, conducting them properly helps a company obtain legitimacy from stakeholders, send positive signals to potential investors, and is believed to affect the company's financial performance. However, economic uncertainty often makes it difficult for companies to turn a profit and pushes them into financial distress. Therefore, this study aims to determine whether financial distress can affect the correlation between CSR and company financial performance.  This study includes nine company samples selected through purposive sampling and involves secondary data analyzed quantitatively using panel data regression and MRA.  ROA and ROE, as proxies for financial performance, are the dependent variables in this study; CSR is the independent variable; and financial distress is the moderating variable. The results of this study suggest that CSR has a positive effect on financial performance and that financial distress negatively moderates the correlation between CSR and financial performance.